Circ-ZFR Promotes Progression of Bladder Cancer by Upregulating WNT5A Via Sponging miR-545 and miR-1270 - Luo, Liping; Miao, Pingping; Ming, Yao; Tao, Jie; Shen, Hongchun (Frontiers in Oncology, 2021)
Background Bladder cancer is one of the most common cancers all over the world. CircZFR is a circular RNA and has been implicated in tumor generation and invasion. However, the exact role of circZFR in the development of bladder cancer (BCa) remains unknown. This study aimed to investigate the function of circZFR in BCa, and further to probe into the association between circ-ZFR, miR-545/miR-1270 and WNT5A. Methods The expression of circZFR in BCa was quantified by qRT-PCR and was positively correlated with the prognosis of BCa patients. Next, the stable knockdown of circZFR BCa cell lines was established and the resulting capacities of proliferation, migration and invasion were measured. The association of circZFR with miR-1270/miR-545 was predicted by circinteractome prediction, and was confirmed by luciferase assay as well as RNA pull down assay. Furthermore, miRNA inhibitors, WNT5A overexpression and Pearson correlation analysis were used to examine the relationship between circZFR, miR-1270/miR-545 and WNT5A. Results The expression of CircZFR was up-regulated both in BCa tissues and in BCa cell lines, and was positively correlated with patient survival rates. Blocking of circZFR’s expression by RNA inhibitors suppressed the proliferation, migration and invasion of BCa cells both in vitro and in vivo. On the other hand, overexpression of target miRNA supported that circZFR directly interact with miR-545 and miR-1270. Moreover, we demonstrated that circZFR promotes the progression of BCa by upregulating WNT5A’s expression via sponging miR-545 and miR-1270. Conclusions CircZFR promotes the proliferation, migration and invasion of BCa cells by upregulating WNT5A signaling pathway via sponging miR-545 and miR-1270. These results provide new insights into the molecular mechanism of circZFR in BCa progression, and more important, a novel target for BCa clinical treatment.